The challenges of quranic mode of dressing: a “terror” to the Student of Nigerian universities (2010)
Nigerian Institutions of higher learning witness the emergence of various social vices such as raping, student abduction, joining of bad gang, and so on. This makes the university campuses to experience unrest, insecurity for both male and female students and undue harassment. The factor could not be absolved from the Nigerian youth subculture as manifested in their non-conventional mode of dressing which more often than not attracts members of the opposite sex. The paper examines the Quranic phraseologies in determining the Islamic perceptions on mode of dressing for both male and female Muslims. The concept of terrorism from the semantic and Islamic perspectives, factors that led to social vices which translate into terrorism among the students, lecturers, and management. Reactions generated by the return of Hijab, Khimar and Niqab into the campuses were critically examined focusing on their negative and positive effects.